2010
DOI: 10.1007/s10557-010-6215-2
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony Stimulating Factor Treatment of Chronic Myocardial Infarction

Abstract: These data clearly show that G-CSF treatment was unable to restore cardiac function impaired by myocardial infarction either with classical approach or long term low dose administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…These results highlight that the effects of G-CSF treatment, which were expected to be more pronounced in the acute phase, might also occur in the chronic phase, without antiapoptotic activity or the formation of new vessels [46]. On the other hand, it was recently reported that G-CSF treatment initiated 4 weeks after myocardial infarction in rats did not improve cardiac function [47]. Collectively, these observations suggest that G-CSF mediates its effects by altering the cardiac remodeling process through modulation of cell infiltration, collagen remodeling, and neoangiogenesis.…”
Section: Inflammation and Healing Processmentioning
confidence: 72%
“…These results highlight that the effects of G-CSF treatment, which were expected to be more pronounced in the acute phase, might also occur in the chronic phase, without antiapoptotic activity or the formation of new vessels [46]. On the other hand, it was recently reported that G-CSF treatment initiated 4 weeks after myocardial infarction in rats did not improve cardiac function [47]. Collectively, these observations suggest that G-CSF mediates its effects by altering the cardiac remodeling process through modulation of cell infiltration, collagen remodeling, and neoangiogenesis.…”
Section: Inflammation and Healing Processmentioning
confidence: 72%
“…Several experimental animal studies [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] and clinical trials [19][20][21][22][23] have examined the effects of G-CSF therapy on acute or chronic MI. However, the effects of G-CSF therapy remain controversial, which may relate to discrepancies in protocols and methodology in those studies [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, authors did not find differences in LVEF between G-CSF and placebo at 1 year. This is not surprising, given the evidence of inefficacy, or even harmful effects, of G-CSF when administered in a late phase after myocardial injury 15 16. In the FIRSTLINE-AMI trial, the 12-month LV-function evaluation was performed by 2-D echocardiography in 30 patients with acute STEMI.…”
Section: Discussionmentioning
confidence: 99%